Delegation of power of attorney and identification of related legal works - POULADI, ALI; GHOLAMI, JAHANBAKHSH; GHANBARPOUR, BEHNAM (The journal of contemporary issues in business and government, 2021)
In the notarial tradition, there is a common document called power of attorney, according to which the power of attorney is delegated to a new lawyer and brings to mind an institution similar to power of attorney or power of attorney, but in an in-depth study, the difference between power of attorney and power of attorney It is obvious that after delegating the powers of the delegating lawyer, the said authority disappears and the powers are completely transferred to the new lawyer; However, in the power of attorney of the previous lawyer, he is still the deputy of his client, despite his former authority, he temporarily transfers his position to a new lawyer, which, of course, is not explicit in the expressions of these two. It should be considered that the words were forged with a purpose and no word was forged and created by an unreasonable author and a philosophy was born for it. The desired difference can be easily discovered and achieved.